Cambios en el léxico eslovaco influidos por los cambios sociopolíticos - Kovachova Rivera de Rosales, Valeria (Eslavística Complutense, 2007)
The vocabulary of a language is a subsystem that requires knowledge of the reality of a country for its proper use. Socio-political changes in Slovakia since 1989 have had a huge impact on the vocabulary of its language. An unnecessary part of the vocabulary has been scrapped, and it has been imperative to expand the vocabulary with indispensable terms in order to deal with the new social, economic, and cultural situation. Vocabulary already known and widely used before 1948 is currently often being retrieved.